Strategi Usaha UMKM Cafe Oma Rahmah - Vivi Nila Sari; Utari Amalia Putri; Julia Rahmi; Olvia Safira; Suci Indah Sari; Sintia Oktaviani (Fakultas Teknik Universitas Cenderawasih, 2023)
MSMEs Oma Cafe Rahmah is a micro, small and medium business engaged in the culinary field, located in Padang Lubuk Begalung. This cafe offers a wide range of traditional and innovative dishes with regional flavours, which has made it a popular culinary destination in the area. MSMEs Oma Cafe Rahmah implements a strategy that focuses on the quality and authenticity of the dishes served. They use fresh, high-quality local ingredients and combine traditional recipes with a modern twist to create interesting and delicious menus. This reflects their commitment to preserving the region's culinary heritage, while providing a unique culinary experience for customers. In addition, MSMEs Oma Cafe Rahmah also prioritizes friendly and professional service. They pay special attention to customer needs and preferences, creating a warm and comfortable atmosphere in the cafe. This has built a strong relationship between MSMEs Oma Cafe Rahmah and its customers, which contributes to the success and sustainability of this business. In the context of the local economy, the existence of MSMEs Oma Cafe Rahmah has had a significant positive impact. This venture creates jobs for local people and in collaboration with local farmers and suppliers, boosts economic growth in the area. Through innovation in the culinary field, MSMEs Oma Cafe Rahmah has proven that micro, small and medium enterprises can play an important role in the development of the local economy. Their success shows that with a commitment to quality, authenticity, and good service, MSMEs can build a strong and sustainable reputation in the culinary industry.